Analisis Tingkat Kerawanan Bencana Banjir di Kota Bandar Lampung Berbasis GIS (Geographic Information System) dan Citra Landsat 8 Oli - Ramadhani, M. Asvi; Amin, M.; Ridwan, Ridwan; Tusi, Ahmad (abe.fp.unila.ac.id, 2023)
Floods in the city of Bandar Lampung are events that occur every year. This has a detrimental impact on humans and the environment, especially during the rainy season where floods often occur. To reduce the impact of human and environmental losses due to floods, this can be done through mitigating flood- prone areas by mapping flood-prone areas using the GIS 10.3 application with the overlay method by combining the parameters used and weighting each parameter to be produce a flood hazard map. This study aims to determine areas that have high flood potential, the main factors causing flooding and to determine the flood vulnerability class in each area of Bandar Lampung City. The parameters used in this study are Land Form, Rainfall, Soil Type, Land Slope, Land Altitude and Building Density. The analysis technique was carried out by giving weights to each environmental parameter and overlay techniques (tumpeng stacking maps) using the GIS application, analysis of building density levels using Landsat 8 image interpretation OLI Band 5 and Band 6. The results showed that the main factors causing flooding in Bandar City Lampung, namely high and evenly distributed rainfall in the city of Bandar Lampung reaching 3000 mm/year. Districts with a very high level of flood vulnerability are in the Bumi Waras District, covering an area of 13% of the administrative area of the District. Then areas that have a high level of flood vulnerability include Panjang 9% and East Betung Bay 4% of the area.North Betung Bay 9% and East Betung Bay 3.17% of the area. Keywords: ArcGis, Flood, Vulnerability, Weighting.